The occurrence of enteroparasites in schoolchildren in the Northeast Region: an integrative Review / A ocorrência de enteroparasitos em escolares na Região Nordeste: uma revisão integrativa - Daniela Calumby de Souza Gomes; Sâmea Keise de Oliveira Silva; Maria Ágda Correia Lemos; Karwhory Wallas Lins da Silva; Aldenir Feitosa dos Santos; Thiago José Matos Rocha (Universidade Estadual de Alagoas, 2020)
Intestinal parasitoses represent a serious public health problem. They are related to socioeconomic and environmental factors that are responsible for the quality of life, sanitary conditions and nutritional status of individuals in a population. Enteroparasitoses are diseases promoted by helminths or protozoans that live in an endoparasitic relationship, lodging in their host's digestive system. Brazil, as an underdeveloped tropical country, has a favorable climate and socioeconomic situation for the occurrence of parasitic diseases. This work aimed to address through an integrative review the occurrence of enteroparasites in human infections in the northeast region. A descriptive integrative review study was carried out, using scientific content sites such as PubMed, LILACS, SCIELO and Google Academic where the keywords "Enteroparasites", "Public Health" and "Socioeconomic conditions" were used as research sources, "Northeast Region". The bibliographic search resulted in 601 articles, of which 14 were selected after analyzing the inclusion criteria. The state of Paraíba was the one with the largest number of articles published, followed by the state of Piauí. The state of Rio Grande in the North did not present any article published during the analyzed period. The most used methodology was spontaneous sedimentation. In the research conducted in the state of kkkk, Estrongyloides stercoralis was isolated from 2 stool samples, observed using the Rugai method. The species Giardia lamblia, Entamoeba coli and Entamoeba histolytica-dispar, were the most cited protozoa in the articles involved in the research. Among the helminths, Ascaris lumbricoides, Enterobius vermicular and Trichuris trichiuria were the most reported. The high prevalence of enteroparasites indicates the lack of effective public hygiene policies in schools as well as the poor sanitary, social and environmental conditions of the population studied.